Perioperative Tight Glucose Control Reduces Postoperative Adverse Events in Nondiabetic Cardiac Surgery Patients - J Bláha; Miloš Mráz; Petr Kopecký; Martin Stříteský; Michal Lipš; Michal Matias; Jan Kunstýř; Michal Pořízka; Tomáš Kotulák; I. Kolnikova; Barbara Šimanovská; M. Zakharchenko; et al. (2015)
Tight glucose control (TGC) reduces morbidity and mortality in patients undergoing elective cardiac surgery, but only limited data about its optimal timing are available to date.The purpose of this article was to compare the effects of perioperative vs postoperative initiation of TGC on postoperative adverse events in cardiac surgery patients.This was a single center, single-blind, parallel-group, randomized controlled trial.The setting was an academic tertiary hospital.Participants were 2383 hemodynamically stable patients undergoing major cardiac surgery with expected postoperative intensive care unit treatment for at least 2 consecutive days.Intensive insulin therapy was initiated perioperatively or postoperatively with a target glucose range of 4.4 to 6.1 mmol/L.Adverse events from any cause during postoperative hospital stay were compared.In the whole cohort, perioperatively initiated TGC markedly reduced the number of postoperative complications (23.2% vs 34.1%, 95% confidence interval [CI], 0.60-0.78) despite only minimal improvement in glucose control (blood glucose, 6.6 ± 0.7 vs 6.7 ± 0.8 mmol/L, P < .001; time in target range, 39.3% ± 13.7% vs 37.3% ± 13.8%, P < .001). The positive effects of TGC on postoperative complications were driven by nondiabetic subjects (21.3% vs 33.7%, 95% CI, 0.54-0.74; blood glucose 6.5 ± 0.6 vs 6.6 ± 0.8 mmol/L, not significant; time in target range, 40.8% ± 13.6% vs 39.7% ± 13.8%, not significant), whereas no significant effect was seen in diabetic patients (29.4% vs 35.1%, 95% CI, 0.66-1.06) despite significantly better glucose control in the perioperative group (blood glucose, 6.9 ± 1.0 vs 7.1 ± 0.8 mmol/L, P < .001; time in target range, 34.3% ± 12.7% vs 30.8% ± 11.5%, P < .001).Perioperative initiation of intensive insulin therapy during cardiac surgery reduces postoperative morbidity in nondiabetic patients while having a minimal effect in diabetic subjects.